Adsorption and dimerisation of thiol molecules on Au(111) using a Z-matrix approach in density functional theory - Ford, M.; Hoft, R.; Gale, Julian (Taylor & Francis Ltd, 2006)
The adsorption energetics of methanethiolate and benzenethiolate on Au(111) have been calculated using periodic density functional theory (DFT), based on the SIESTA methodology, with an internal coordinates implementation for geometry input and structure optimisation. Both molecules are covalently bound with interaction energies of 1.85 and 1.43 eV for methanethiolate and benzenethiolate, respectively. The preferred binding site is slightly offset from the bridge site in both cases towards the fcc-hollow. The potential energy surfaces (PES) have depths of 0.36 and 0.22 eV, the hollow sites are local maxima in both cases, and there is no barrier to diffusion of the molecule at the bridge site. The corresponding dimers are weakly bound for methanethiolate and benzenethiolate, with binding energies of 0.38 and 0.16 eV, respectively, and the preferred binding geometry is with the two sulphur atoms close to adjacent atop sites. The barrier to dissociation of the dimer dimethyl disulphide is estimated to lie between 0.3 and 0.35 eV.